Riparian plant diversity in relation to artisanal mining sites in Cikidang River, Banten, Indonesia - Noverita Dian Takarina; Ika Lina Sinaga; Tri Rifqoh Umi Kulsum (Society for Indonesian Biodiversity, 2021)
Abstract. Takarina ND, Sinaga IL, Kultsum TR. 2021. Riparian plant diversity in relation to artisanal mining sites in Cikidang River, Banten, Indonesia. Biodiversitas 22: 401-407. Artisanal mining usually occurs in gold mining activities near the river banks and consequently, this will affect the downstream ecosystem include riparian habitat and its plant diversity. Here, this study aimed to assess the effects of artisanal mining sites on the riparian plant diversity in Cikidang River, Lebak District, Banten Province, Indonesia. The study was conducted by placing 10 sampling stations along 4 km of Cikidang River with width of 20 m. Riparian plant species were collected and identified from 10 m x 10 m sampling plots in each station. Plant diversity was assessed using Shannon-Wiener, Simpson, Margalef, and Pielou indices. There were in total 18 families and 42 plant species have been identified. Compositae and Poaceae were plant families that common here. Ageratum conyzoides was the most common species followed by Impatiens platypetala, Cibadium surinamense, Wollastonia biflora, Calliandra calothyrsus, and Pityrogramma calomelanos. Shannon-Wiener diversity index was in the range of 1.040-1.561. There was a positive correlation between riparian diversity with the distance to mining sites with decreasing diversity trends toward artisanal mining sites. Riparian habitats located far (> 1 km) from the mining sites have more species. While species observed in riparian habitats near (0.3-1 km) the mining sites were accounted only for 26.1% of total species found. To conclude, the presence of artisanal mining sites can affect the nearby riparian plant diversity.